Comparison of the value of novel rapid measurement of myoglobin, creatine kinase, and creatine kinase-MB with the electrocardiogram for the diagnosis of acute myocardial infarction. Issue 4 (April 1994) - Lee, H. S.; Cross, S. J.; Garthwaite, P.; Dickie, A.; Ross, I.; Walton, S.; Jennings, K.
Abstract : OBJECTIVE–To determine whether serum myoglobin, creatine kinase, and creatine kinase-MB measured at admission by rapid, compact, and easy to use automated quantitative analysers (results within 10 min) helped the early identification of acute myocardial infarction. The results were compared with the data obtained from the electrocardiograms recorded at admission. DESIGN–A prospective study. SETTING–Coronary care unit. PATIENTS–94 consecutive patients with suspected myocardial infarction. Myocardial infarction was subsequently confirmed in 44 patients and excluded in 50. METHODS–All admission serum myoglobin, creatine kinase, and creatine kinase-MB were measured by clinical staff using analysers in the coronary care unit. An admission electrocardiogram was obtained from all patients. RESULTS–The sensitivity, specificity, and predictive accuracy for diagnosing myocardial infarction were: electrocardiogram 68%, 100%, and 85%; myoglobin 57%, 100%, and 80%; creatine kinase (threshold of 190 U/l) 34%, 98%, and 68%; creatine kinase-MB (threshold of 25 U/l) 43%, 100%, and 73%. When the electrocardiographic and myoglobin data were combined the sensitivity improved to 91%, diagnostic accuracy to 96%, with specificity of 100%. The results for the electrocardiogram and creatine kinase-MB were 80%, 90%, 100% respectively and those for the electrocardiogram with creatine kinase were 80%, 89%, 98% respectively. CONCLUSIONS–Admission myoglobin, creatine kinase, and creatine kinase-MB measurements were not as useful as the electrocardiogram for the diagnosis of acute myocardial infarction. Combining the electrocardiogram and myoglobin data substantially improved the sensitivity and predictive accuracy for the diagnosis of acute myocardial infarction.